Birth weight and postnatal microbial exposures predict the distribution of peripheral blood leukocyte subsets in young adults in the Philippines. (11th October 2017) - McDade, T. W.; Jones, M. J.; Miller, G.; Borja, J.; Kobor, M. S.; Kuzawa, C. W.
Abstract : The immune system not only provides protection against infectious disease but also contributes to the etiology of neoplastic, atopic, and cardiovascular and metabolic diseases. Prenatal and postnatal nutritional and microbial environments have lasting effects on multiple aspects of immunity, indicating that immune processes may play important roles in the developmental origins of disease. The objective of this study is to evaluate the association between birth weight and the distribution of leukocyte (white blood cell) subsets in peripheral blood in young adulthood. Postnatal microbial exposures were also considered as predictors of leukocyte distribution. Participants ( n =486; mean age=20.9 years) were drawn from a prospective birth cohort study in the Philippines, and analyses focused on the following cell types: CD4 T lymphocytes, CD8 T lymphocytes, B lymphocytes, natural killer cells, monocytes, granulocytes. Higher birth weight was a strong predictor of higher proportion of CD4 T lymphocytes (B=0.12, s.e. =0.041, P =0.003), lower proportion of CD8 T lymphocytes (B=−0.874, s.e. =0.364, P =0.016), higher CD4:CD8 ratio (B=1.964, s.e. =0.658, P =0.003), and higher B lymphocytes (B=0.062, s.e. =0.031, P =0.047). Measures of microbial exposure in infancy were negatively associated with proportions of B lymphocytes and granulocytes, and lower CD4:CD8 ratio. Leukocytes are the key regulators and effectors of innate and specific immunity, but the origins of variation in the distribution of cell type across individuals are not known. Our findings point toward nutritional and microbial exposures in infancy as potentially important determinants of immune-phenotypes in adulthood, and they suggest that leukocyte distribution is a plausible mechanism through which developmental environments have lasting effects on disease risk in adulthood.